Functional properties of different collagen scaffolds to create a biomimetic niche for neurally committed human induced pluripotent stem cells (iPSC) - Pietrucha, Krystyna; Zychowicz, Marzena; Podobinska, Martyna; Buzanska, Leonora (Folia Neuropathologica, 2017)
The biomimetic, standardized conditions for in vitro cultures of human neural progenitors derived from induced pluripotent stem cells (hiPSC-NPs) should meet the requirements to serve as the template and protective environment for therapeutically competent cell population. In this study, two different collagen scaffolds: bi-component consisting of collagen and chondroitin sulphate (Col-CS), and collagen modified by crosslinking agent 2,3-dialdehyde cellulose (Col-DAC) have been used for the first time to encapsulate hiPSC-NPs and compared for the ability to create permissive microenvironment enabling cell survival, growth and differentiation. In our previous report, physicochemical comparison of the scaffolds revealed different elasticity, and diverse size and distribution of the pores within the 3D structure. Binary systems of Col-CS and Col-DAC tested in the current study have the correct balance of properties to serve as a biomimetic niche: they accommodate hiPSC-NPs sustaining their ability to proliferate and differentiate into neural lineages. However, a dense, network structure and rounded in shape pores of the Col-DAC microenvironment resulted in differential cell distributions within the scaffolds, with a tendency for augmented formation of highly proliferating cell aggregates as compared to Col-CS scaffolds. In contrast, Col-CS, which exhibited formation of the network of ellipsoidal and inner interconnected parallel pore channels, promoted enhanced cell viability and neuronal differentiation.